The historical ecological footprint: From over-population to over-consumption. (January 2016) - Toth, Gergely; Szigeti, Cecília
Abstract: The ecological risk from over-population has been recognized sinceMalthus (1798) . GDP growth per capita in agriculture disproved his pessimism but, since the Club of Rome and its case on Limits to Growth more recently there has been concern that there is a parallel risk from such growth in terms of ecological footprints (EF). Authors have developed a GDP/EF correlation function and calculated the ecological footprint (EF) from 10, 000 B.C. till 1960, using historical statistics, with the method of backcasting (Brandes and Brooks, 2005 ). 1 In all major indicators growth patterns have been dominating, not only since the industrial revolution, but in the known history of mankind. From data since 1961, we calculate the correlation between GDP and the ecological footprint and have been able to determine long time data series of population, GDP, biocapacity and EF. Our findings are first: the main driver of growth and environmental degradation is not population per se, but consumption patterns and levels multiplied by the number of consumers, especially in developed economies, as the I = PAT equation recognized (Ehrlich and Holdren, 1971 ). In fact, as we approach to today, population, which used to be the key driver to growth and environmental degradation, becomes the least important driver, especially in the last two decades. Second: change is not incremental or linear as assumed in much mainstream economics: in line with Schumpeter's bunching and swarming and it jumps and leaps asymmetrically, as in our finding of such a leap (the 7th) between the 1930s and 1970s. Third: the dominant paradigm legitimizing growth (from the late 18th century) while already challenged by many since the Club of Rome and other reports should be revisited in terms of the concept of 'fullness' in the sense that while the earth in 1776 was roughly 10 per cent full, by 2008 this figure was over 150 per cent.